Pembelajaran Sejarah Menjadi Bermakna dengan Pendekatan Kontektual - Yeni Asmara (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2019)
The purpose of this study was to determine the history of learning with a contextual approach. This research is in the form of a Library Study (Library Research) as an effort to collect information and data by utilizing written sources in the library such as books, newspapers, magazines, documents that are relevant to the issues discussed. The results of the study, through learning history teachers can develop students' understanding of the past by learning that can connect between historical material with real situations around students, so students can describe past events as they are in history lessons. The innovation is known as contextual learning that has principles, principles in its application by linking the material learned with the real life of daily students, both within the family, school, community and citizens, with the aim to find meaning the material for his life.From the results of this study, it can be concluded that contextual learning can help students learn past history with real situations around them. Keywords: Learning, Contextual Approach